Can Social Capital Dimensions Optimize Operational Performance? - Mediating Role of Supply Chain Collaboration - Poramet Saengon; Kulnaree Maneechote; Aksorn Sawasdee (International Journal of Supply Chain Management, 2019)
This study examines the role of social capital dimensions such as structural capital, cognitive capital, and relational capital on the operational performance of the textile industry of Thailand with the help of supply chain collaboration as a mediator. The data is collected from supply chain managers of the textile companies that are operating in Thailand. The survey questionnaire was used for data collection, and PLS-SEM was used for analysis. The results show that all the dimensions of social capital, such as structural capital, cognitive capital, and relational capital, has the ability to improve the operational performance of the companies. Moreover, supply chain collaboration has also played a vital role in mediation between the social capital and operational performance of the company. This study suggested to the policymakers that they should improve the social capital and supply chain management that is necessary for the operational performance of the company.